A new oral amoebicid (RO 7-0207) in the treatment of intestinal amoebiasis - S. H. Pudjiadi; Sunoto Sunoto; Suharjono Suharjono; Nartono Kadri (Paediatrica Indonesiana, 1973)
Amoebiasis is a widespread disease with the diffusion of the parasitevarying more with hygienic than geopraphic conditions. The incidencevaries from country to country. Soysa (1971) has estimated that ten per cent of the world-population suffers from amoebiasis. Udani et al. (1971) said that "it will not he an exaggaration to state that everyhody in a developing country either had, has or will have amoebic infection". InIndonesia, the incidence varies according to environmental, socia-economic, hygienic and sanitary conditions (Pudjiadi, 1971).